2006
DOI: 10.1007/s10620-005-9053-5
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease and Streptococcus bovis

Abstract: Evidence suggests a trend for a higher fecal carriage rate of Streptococcus bovis in adult patients with inflammatory bowel disease (IBD). This study defines the fecal carriage rate of S. bovis among children with IBD compared to controls. Subjects with IBD were prospectively enrolled from the patient population of a pediatric gastroenterology practice. Stool samples from IBD patients as well as controls were analyzed within 24 hr for the presence of S. bovis. The study enrolled 47 patients with IBD and 34 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…It can also be detected in human fecal samples. Its presence in humans is usually related to serious diseases such as colon carcinoma/ adenoma, inflammatory bowel disease (IBD), endocarditis, or bacteremia (Potter et al 1998;Dubrow et al 1991;Nielsen et al 2007;Sharara et al 2013;Teitelbaum and Triantafyllopoulou 2006).…”
Section: Cancermentioning
confidence: 99%
“…It can also be detected in human fecal samples. Its presence in humans is usually related to serious diseases such as colon carcinoma/ adenoma, inflammatory bowel disease (IBD), endocarditis, or bacteremia (Potter et al 1998;Dubrow et al 1991;Nielsen et al 2007;Sharara et al 2013;Teitelbaum and Triantafyllopoulou 2006).…”
Section: Cancermentioning
confidence: 99%
“…49–56 While 3 small studies including 13–46 controls and corresponding 11 colorectal cancer, 47 pediatric inflammatory bowel disease (IBD) and 56 polyp patients failed to show any association, 5254 five other studies found that SB carriage (either in stool or antibodies) rates were significantly higher in cancer patients than in controls. Interestingly, 3 studies also showed that patients with premalignant lesions (IBD or polyps) had intermediate SB carriage rate between cancer cases and controls.…”
Section: Epidemiological Studies Of Microbiome and Colorectal Cancermentioning
confidence: 99%
“…A marked resurgence of interest in the gastrointestinal commensal flora and local host-microbe interactions was observed since it was recognized that intestinal bacteria could be implicated in the pathogenesis of several inflammatory diseases like Crohn's disease or ulcerative colitis [17]. Both diseases are commonly suspected to result from altered host responses to intestinal bacterial flora [18], and are associated with cancer risk [17,19-21].…”
Section: Bacterial Pathogens and Cancermentioning
confidence: 99%
“…Both diseases are commonly suspected to result from altered host responses to intestinal bacterial flora [18], and are associated with cancer risk [17,19-21]. Accordingly, World Health Organization considered bacteria as possible causative agents for cancer development.…”
Section: Bacterial Pathogens and Cancermentioning
confidence: 99%